Oroxylin A promotes retinal ganglion cell survival in a rat optic nerve crush model. - Shu-Fang Lin; Jia-Ying Chien; Kishan Kapupara; Chi-Ying F Huang; Shun-Ping Huang (PLoS ONE)
Purpose To investigate the effect of oroxylin A on the survival of retinal ganglion cells (RGC) and the activation of microglial cells in a rat optic nerve (ON) crush model. Methods Oroxylin A (15mg/Kg in 0.2ml phosphate-buffered saline) or phosphate-buffered saline (PBS control) was immediately administered after ON crush once by subcutaneous injection. Rats were euthanized at 2 weeks after the crush injury. The density of RGC was counted by retrograde labeling with FluoroGold and immunostaining of retina flat mounts for Brn3a. Electrophysiological visual function was assessed by flash visual evoked potentials (FVEP). TUNEL assay, immunoblotting analysis of glial fibrillary acidic protein (GFAP), inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in the retinas, and immunohistochemistry of GFAP in the retinas and ED1 in the ON were evaluated. Results Two weeks after the insult, the oroxylin A-treated group had significantly higher FG labeled cells and Brn3a+ cells suggesting preserved RGC density in the central and mid-peripheral retinas compared with those of the PBS-treated group. FVEP measurements showed a significantly better preserved latency of the P1 wave in the ON-crushed, oroxylin A-treated rats than the ON-crushed, PBS treated rats. TUNEL assays showed fewer TUNEL positive cells in the ON-crushed, oroxylin A-treated rats. The number of ED1 positive cells was reduced at the lesion site of the optic nerve in the ON-crushed, oroxylin A-treated group. Increased GFAP expression in the retina was reduced greatly in ON-crushed, oroxylin A-treated group. Furthermore, administration of oroxylin A significantly attenuated ON crush insult-induced iNOS and COX-2 expression in the retinas. Conclusions These results demonstrated that oroxylin A hasss neuroprotective effects on RGC survival with preserved visual function and a decrease in microglial infiltration in the ONs after ON crush injury.